Adaptation to the impacts of climate change in Kigali, Rwanda: Challenges and Opportunities - Pacifique IRAGUHA (My University, 2025)
Climate change remains one of the most pressing global challenges, exerting profound impacts on ecosystems, economies, and human well-being. Rising global temperatures, altered weather patterns, and the increased frequency of extreme events threaten critical sectors such as agriculture, water supply, and public health. These impacts are particularly severe in regions with limited adaptive capacity, where they exacerbate existing social and economic vulnerabilities. Developing effective adaptation strategies is essential to building resilient societies and safeguarding future development gains. This study examines various adaptation responses to the impacts of climate change across multiple sectors and geographical settings. It aims to identify successful strategies, evaluate their effectiveness, and design adaptable frameworks suited to local needs. The research also seeks to uncover key barriers to adaptation, including financial, technological, and institutional challenges, and to offer recommendations that enhance community participation and strengthen institutional resilience. At this early phase, the study applies a mixed-methods research design, incorporating both qualitative and quantitative approaches. Initial work involves developing surveys and conducting interviews with community members, decision-makers, and field practitioners, alongside gathering baseline climate data and reviewing case studies of adaptation practices. Geographic Information Systems (GIS) are being introduced to map vulnerable areas and monitor trends over time. Participatory workshops are also being planned to integrate local knowledge and foster collaboration among key stakeholders, ensuring that adaptation measures are practical and sustainable. Preliminary insights highlight the effectiveness of community-led initiatives compared to top-down strategies. Promising practices, including climate-resilient agriculture, decentralized water management, and nature-based solutions, have begun to emerge. However, challenges such as funding shortages, technological gaps, and weak governance structures persist. Since the research is ongoing, further analysis is necessary to validate these early findings and to develop comprehensive adaptation policies that are equitable, sustainable, and responsive to evolving climate risks